Discussion of Municipal Finances in Perspective: A Look at Interjurisdictional Spending and Revenue Patterns - McCaffery, Jerry (Journal of Accounting Research, 1977)
Jerry McCaffery, Discussion of Municipal Finances in Perspective: A Look at Interjurisdictional Spending and Revenue Patterns, Journal of Accounting Research, Vol. 15, Studies on Measurement and Evaluation of the Economic Efficiency of Public and Private Nonprofit Institutions (1977), pp. 202-205